Pemanfaatan Limbah Daun Cengkeh menjadi Minyak Cengkeh di Desa Bajulan Kecamatan Loceret Kabupaten Nganjuk - Avisema Sigit Saputro; Nugraheni Hadiyanti; Virgian Galuh Agusty (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2023)
The use of cloves is usually for food and medicinal raw materials. Clove leaf waste can be distilled into oil that is useful for traditional medicine and perfume. This community service activity aims to increase the knowledge and insight of the people of Bajulan Village, Loceret District, Nganjuk Regency in the utilization of clove leaf waste into clove oil. Implementation of activities from August to September 2022 as a collaboration of the community service team from the Faculty of Agriculture, Kadiri University, and training participants in Bajulan Village, Loceret District, Nganjuk Regency. The method of implementing this activity includes preparation, program socialization, presentation of material to the target, training on oil refining from clove leaves, mentoring, and activity evaluation. The existence of these community service activities can open insights and introduce innovations to training participants about the utilization of clove plant waste. Socialization and training on clove leaf oil refining went well, and the community was interested in developing it. This activity hopes to provide added value to clove leaf waste and an effort to deal with organic waste in the people of Bajulan Village, Loceret District, Nganjuk Regency.  Pemanfaatan cengkeh biasanya hanya untuk makanan dan bahan baku obat. Limbah daun cengkeh ternyata bisa disuling menjadi minyak yang berguna untuk pengobatan tradisional dan parfum. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan pengetahuan dan wawasan masyarakat Desa Bajulan Kecamatan Loceret Kabupaten Nganjuk dalam pemanfaatan limbah daun cengkeh menjadi minyak cengkeh. Pelaksanaan kegiatan pada bulan Agustus sampai September 2022 sebagai kerjasama tim pengabdian masyarakat Fakultas Pertanian Universitas Kadiri dan peserta pelatihan di Desa Bajulan Kecamatan Loceret Kabupaten Nganjuk. Metode pelaksanaan pada kegiatan ini meliputi persiapan, sosialisasi program dengan pemaparan materi kepada peserta, pelatihan pembuatan minyak dari limbah daun cengkeh, pendampingan, dan evaluasi kegiatan. Adanya kegiatan pengabdian masyarakat tersebut mampu membuka wawasan dan mengenalkan inovasi kepada peserta pelatihan tentang pemanfaatan limbah tanaman cengkeh. Sosialisasi dan pelatihan pembuatan minyak cengkeh berjalan dengan baik dan muncul ketertarikan peserta untuk mengembangkannya. Kegiatan ini diharapkan mampu memberikan nilai tambah limbah daun cengkeh dan sebagai usaha mengatasi permasalahan sampah organik di Desa Bajulan Kecamatan Loceret Kabupaten Nganjuk.